Exosomal novel-miRNA-126 mediates vascular endothelial dysfunction by targeting AhR-NLRP3 pathway in nonalcoholic steatohepatitis - Qiuhe Chen; Lifeng Ye; Liting Huang; Hongjing You; Xiaoying Yu; Ke Wang; Shengtao Xiong; Weiyan Liao; Xiao Wang; Haiyan Li; Yang Chen (Scientific Reports)
Abstract Nonalcoholic steatohepatitis (NASH) is an increasingly prevalent liver disease associated with obesity and its complications. Recent studies have underscored a significant correlation between NASH and an elevated risk of cardiovascular diseases. However, the precise mechanisms of inter-organ communication between the liver and vascular endothelium are not fully understood. In this study, we established a NASH mouse model using a methionine-choline-deficient diet to investigate the role of liver-derived exosomes in modulating vascular endothelial dysfunction during NASH progression. Utilizing both in vivo and in vitro experimental approaches, we observed vascular dysfunction and activation of the NLRP3 inflammasome in NASH mice. Further analyses identified exosomal novel-miRNA-126 as a critical mediator influencing vascular endothelial dysfunction. This miRNA augments NLRP3 transcription and accelerates NLRP3 inflammasome activation by targeting the aryl hydrocarbon receptor (AhR). These findings offer novel insights into the mechanisms of liver-to-vascular communication and suggest new avenues for the prevention and therapeutic intervention of cardiovascular complications in NASH patients.